Critical study of bandwidth management strategies for internet services: case study Midlands State University - Vushemasimba, Norrence (Midlands State University, 2018)
The internet has become a key resource at Midlands State University for research and communication. The institution is also experiencing high students’ population which in turn has led to more demand for bandwidth. The high students’ population makes the overall available bandwidth shrink leading to slow internet connection making internet an ineffective academic resource. The institution has been responding to slow internet connection by buying more bandwidth which is so uneconomical with bandwidth being an expensive resource. This work is an in depth survey on the causes of bandwidth problems, the basic models and techniques for bandwidth management and its followed by an analysis which is aimed at yielding meaningful suggestions on h on internet usage, educating the users on bandwidth management and looking into how to manage and optimize the bandwidth efficiently. The strategies were evaluated on traffic management, bandwidth allocation and bandwidth restriction. The findings obtained full proof that that traffic management, bandwidth allocation and bandwidth restriction can be used for effective bandwidth management. Suggestion for further research were given such as coming up with policies at the university on internet usage, educating users on bandwidth management and looking into Deep Packet Inspection.